2019
DOI: 10.1007/s10493-019-00373-5
|View full text |Cite
|
Sign up to set email alerts
|

The repellency and toxicity effects of essential oils from the Libyan plants Salvadora persica and Rosmarinus officinalis against nymphs of Ixodes ricinus

Abstract: Essential oils extracted from the leaves of Libyan Rosemary (Rosmarinus officinalis L.), and Miswak (Salvadora persica L.) were evaluated for their acaricidal and repellent effects on Ixodes ricinus L. nymphs (Acari: Ixodidae) using a bioassay based on an 'open filter paper method'. Rosmarinus officinalis leaf essential oil diluted to 0.5 and 1 µl/cm 2 in acetone exhibited, respectively, 20 and 100% tick mortality after about 5 h of exposure. A total of 50 and 95% of I. ricinus nymphs were killed by direct con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Rosemary has economic values owing to its medicinal properties and culinary usage, and it is frequently used in confectionery, perfumery [2,3], and food preservatives, especially meat [4]. Commercially, rosemary and its oil are highly-prized [5]. The plant is also available as dried herbs, with herbalists selling the aromatic and medicinal plants together with its oil in the community pharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary has economic values owing to its medicinal properties and culinary usage, and it is frequently used in confectionery, perfumery [2,3], and food preservatives, especially meat [4]. Commercially, rosemary and its oil are highly-prized [5]. The plant is also available as dried herbs, with herbalists selling the aromatic and medicinal plants together with its oil in the community pharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown a moderate post-ingestive toxicity to S. littoralis for a similar R. officinalis EO (Santana et al, 2014). R. officinalis EOs rich in 1,8-cineole were toxic to larvae of Hyalomma scupense (Djebir et al, 2019) and I. ricinus nymphs (Elmhalli et al, 2019), while an EO rich in α-pinene showed low-moderate toxicity against larvae of R. (B.)…”
Section: Thymus Zygismentioning
confidence: 81%
“…Essential oils are the most studied plant-derived compounds for tick control and prevention [9,16,18,122]. Two effects of essential oils against ticks were observed: acaricidal or repellent effects [9,16,[122][123][124][125][126][127]. They cause various effects against ticks: feeding inhibition [125,128,129], inhibition of chitin synthesis [9,78,129], decrease in growth, development, or reproduction [9,78,125,126,128,130], and affect tick behavior [129].…”
Section: Mechanisms Of Action Of the Essential Oils And/or Their Components Against Ticksmentioning
confidence: 99%
“…Many plants and/or their essential oils have a repellent effect against arthropods [122,126,152,153].…”
Section: Repellent Effectsmentioning
confidence: 99%